Knowledge, Conscience, Consciousness, Awareness, or About the Presence and Use of Artificial Intelligence (AI) in Spiritual Life and Their Challenges - BURLACU, Magdalena (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2024)
The use of artificial intelligence (AI) into spiritual life presents unique challenges and opportunities. This article explores the regulatory deficiencies in the application of AI in religious settings. The existence of controversial platforms such as Biserica GPT emphasizes the need for specific ethical norms designed for spiritual life. The article advocates for an approach that recognizes the capacity of AI to improve communication and social unity, while underscoring ethical concerns and the significance of authentic human spiritual direction. The proposed ethical criteria include transparency, accountability, and the safeguarding of human dignity. They emphasize the need for a cooperative effort between programmers, operators, and those possessing spiritual expertise to ensure that AI is used as a tool rather than functioning as a substitute for authentic spiritual direction.